A review of the Neotropical genus Amazobenna Penny, 1980 with description of a new species and description of the male of Amazobenna reticulata Penny, 1980 (Hemiptera: Fulgoromorpha: Cixiidae) - Viegas, Eduarda Fernanda Gomes; Ale-Rocha, Rosaly (Zootaxa, 2019)
A second species of the genus Amazobenna Penny, 1980, Amazobenna pennyi sp. nov., is described from the Brazil. The new species can be distinguished from Amazobenna reticulata Penny, 1980, the type species of the genus, by the coloration of the body and wing and by the characters of the male genitalia. The description of male of Amazobenna reticulata is also provided and morphology of male and female genitalia of the genus is discussed for the first time. Copyright © 2019 Magnolia Press.
Keywords: Animals; Female; Hemiptera; Male; Male Genital System; Animal; Female; Genitalia, Male; Hemiptera; Male